Assessing relational, emotional, and physical dimensions of young players during the tag games - Gaztelu-Folla, Ioritz; Gonzalez-Artetxe, Asier; Vélaz-Lorente, Íñigo; Los Arcos, Asier (Cuadernos de Psicología del Deporte, 2022)
Many tag games present unstable motor communications between players, that is, the motor communication varies during the play due to role-changing. A holistic point of view provides a more complete assessment of the experience of the players during the traditional tag games. Thus, the aims of the study were to propose and use a specific guide to assess the relational, emotional, and physical dimensions during a traditional motor game in young players. Twenty-two young players took part in the study. The participants played a modification of the classic it motor game for ten minutes. The relational dimension was assessed by observational methodology analysing counter-communications between the tagger and the runner who experienced the counter-communication. The emotional dimension was assessed by the BECS scale of perceived enjoyment and competence. Physical dimension was assessed by differentiating the tagger, the runner, and the target-player measuring the Total Distance covered per second. The relational analysis provided clues about the social relationship of the group. The high values of enjoyment (4.4 ± 0.6) and perceived competence (4.0 ± 0.6) declared by players (suggested the use of the traditional tag game during Physical Education lessons and sport training. The tagger performed significantly greater total distance than the rest of the players (p=.00; Effect Size= 1.53 – 2.76), suggesting that the assessment of the physical dimension during motor games should be carried out differentiating the motor roles. The assessment of the experience of the players during the motor games differentiating by roles and from a holistic point of view could help to optimise the pedagogical plan.